Current state about root coverage using soft-tissue substitutes in the presence of noncarious cervical lesions: A literature review - Aldrin André Huaman-Mendoza; Isabella Neme Ribeiro Dos Reis; Juliana Assef Ganhito; Cassio Volponi Carvalho; Giorgio De Michel; Claudio Mendes Pannuti (Wolters Kluwer Medknow Publications, 2023)
About half of the cases of gingival recession are associated with the noncarious cervical lesion (NCCL), resulting in combined defects (CDs). NCCL negatively affects the root coverage outcomes. In addition, considering the morbidity associated with graft harvesting, soft-tissue substitutes (STSs) appeared as a suitable option for connective tissue grafts for surgical root coverage. Currently, the literature addressing the therapy of CDs employing STSs is scarce. Thus, the present review aimed to update the literature and outline the future perspectives about root coverage of CDs using STSs. A detailed literature search was conducted on MEDLINE, Web of Science, EMBASE, LILACS, Scopus, and Google Scholar databases using keywords and Boolean operators. Randomized clinical trials (2) and case reports (6) were included. None of the selected studies reported any adverse effect using STSs. Based on the limited evidence available, we cannot state that STSs may benefit the periodontal clinical and patient-centered outcomes. Randomized controlled trials are needed to assess the long-term outcomes, surgical approaches, and restorative protocols.